Influence of caries activity and number of saliva donors: mineral and microbiological responses in a microcosm biofilm model (Journal of Applied Oral Science, 2022)
Objective: this study evaluated the mineral and microbiological response of biofilms originating from different types of saliva inoculum with distinct levels of caries activity. Methodology: the biofilms grown over enamel specimens originated from saliva collected from a single donor or five donors with two distinct levels of caries activity (caries-active and caries-free) or from pooling saliva from ten donors (five caries-active and five caries-free). The percentage surface hardness change (%SHC) and microbiological counts served as outcome variables. Results: the caries activity of donors did not affect the %SHC values. Inoculum from five donors compared to a single donor showed higher %SHC values (p=0.019). Higher lactobacilli counts were observed when saliva from caries-active donors was used as the inoculum (p=0.017). Pooled saliva from both caries activity levels showed higher mutans streptococci counts (p<0.017). Conclusion: Overall, pooled saliva increased the mineral response of the derived biofilms, but all the inoculum conditions formed cariogenic biofilms and caries lesions independently of caries activity.